The land of Ionia : society and economy in the Archaic period - Greaves, Alan M., 1969- (Wiley-Blackwell, 2010)
Incorporating over a century of archaeological research, Greaves offers a reassessment of Archaic Ionia that attempts to understand the region within its larger Mediterranean context and provides a thematic overview of its cities and people.: Seeks to balance the Greek and Anatolian cultural influences at work in Ionia in this important period of its history (700BC to the Battle of Lade in 494BC); Organised thematically, covering landscape, economy, cities, colonisation, warfare, cult, and art; Accesses German and Turkish scholarship, presenting a useful point of entry to the published literat.